2009
DOI: 10.1007/s00595-008-3922-4
|View full text |Cite
|
Sign up to set email alerts
|

Impacted obturator hernia treated successfully with a Kugel repair: Report of two cases

Abstract: Obturator hernia repair has traditionally been performed via an intra-abdominal approach, although laparoscopy is also emerging as a feasible alternative. On the other hand, the Kugel method is a minimally invasive and effective form of repair of groin hernia, but there have been few reports on its use for an incarcerated obturator hernia. We describe how we used the Kugel method to repair an obturator hernia in two patients. Both patients presented with acute intestinal obstruction, necessitating emergency su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Furthermore, obturator hernias occur approximately six times more often in women than in men because of the broader pelvis and larger lumen of the obturator foraman. 7 Alvarez et al reported right-sided inguinal and femoral hernias to be more common than left-sided ones, 5 but there was no signifi cant difference between the incidences of right-sided and left-sided hernias in the incarcerated hernias in the current study.…”
Section: Discussioncontrasting
confidence: 45%
“…Furthermore, obturator hernias occur approximately six times more often in women than in men because of the broader pelvis and larger lumen of the obturator foraman. 7 Alvarez et al reported right-sided inguinal and femoral hernias to be more common than left-sided ones, 5 but there was no signifi cant difference between the incidences of right-sided and left-sided hernias in the incarcerated hernias in the current study.…”
Section: Discussioncontrasting
confidence: 45%
“…Strangulated hernias have been deemed to be an absolute contraindication for the use of a prosthetic mesh [2]. Some groups, however, have reported that a strangulated groin hernia can be repaired safely with a prosthetic mesh [2][3][4][5][6][7]. There is no consensus on the use of prostheses in potentially infected operating fields (after intestinal resection) [8].…”
Section: Introductionmentioning
confidence: 97%
“…21 Most reports describe use of the Kugel patch or flat meshes. 20,22,23 Mesh plug repair may worsen obturator neuralgia because the device shrinks and forms a rigid prosthetic tumor. 24 Therefore, we routinely use flat meshes, such as Bard mesh (CR Bard Inc., Murray Hill, NJ, USA) or ULTRAPRO TM (Ethicon, Somerville, MA, USA), that we can trim to fit the preperitoneal space and cover other hernias simultaneously.…”
Section: Discussionmentioning
confidence: 99%